Effect of Phosphorylated-Extracellular Regulated Kinase 1/2 Inhibitor on Retina from Light-induced Photoreceptor Degeneration - Xin-Yi Ding; Rui-Ping Gu; Wen-Yi Tang; Qin-Meng Shu; Ge-Zhi Xu; Meng Zhang (Chinese Medical Journal, 2018)
Background: The demonstrated role of mitogen-activated protein kinase (MAPK) in both cell apoptosis and the inflammation pathway makes it an attractive target for photoreceptor protection. The aim of this study was to investigate the protective effects of MAPK antagonists against photoreceptor degeneration and retinal inflammation in a rat model of light-induced retinal degeneration. Methods: Sprague Dawley rats were treated with intravitreal injections of MAPK antagonists, inhibitors of p-P38, phosphorylated-extracellular regulated kinase (p-ERK) 1/2, and p-c-Jun N-terminal kinase (JNK) just before they were assigned to dark adaptation. After dark adaptation for 24 h, rats were exposed to blue light (2500 lux) in a light box for 24 h, and then returned to the normal 12-h light/12-h dark cycle. Samples were collected at different time points. MAPK expression during light exposure was examined with immunofluorescence. Photoreceptor death was detected with histopathology and terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) staining. The expression of retinal p-ERK1/2, caspase 3, activated caspase 3, tumor necrosis factor (TNF)-α, and interleukin (IL)-1β was examined by Western blotting. Differences between groups were evaluated using unpaired one-way analysis of variance and least significant difference post hoc tests. Results: MAPKs (P38, ERK1/2, and p-JNK) were phosphorylated and activated in the light injury groups, compared with normal group, and their expressions were mainly elevated in the outer nuclear layer (ONL). Among the selected MAPK antagonists, only the p-ERK1/2 inhibitor attenuated the loss of photoreceptors and the thinning of ONL in light injury groups. Besides, p-ERK1/2 inhibitor refrained light-induced photoreceptor apoptosis, which was presented by TUNEL positive cells. Light injury significantly increased the expression of p-ERK1/2 (1.12 ± 0.06 vs. 0.57 ± 0.08, t = 9.99, P < 0.05; 1.23 ± 0.03 vs. 0.57 ± 0.08, t = 11.90, P < 0.05; and 1.12 ± 0.12 vs. 0.57 ± 0.08, t = 9.86, P < 0.05; F = 49.55, P < 0.001), and induced caspase 3 activating (0.63 ± 0.06 vs. 0.14 ± 0.05, t = 13.67, P < 0.05; 0.74 ± 0.05 vs. 0.14 ± 0.05, t = 16.87, P < 0.05; and 0.80 ± 0.05 vs. 0.14 ± 0.05, t = 18.57, P < 0.05; F = 100.15, P < 0.001), compared with normal group. The p-ERK1/2 inhibitor significantly reduced p-ERK1/2 overexpression (0.61 ± 0.06 vs. 1.12 ± 0.06, t = −9.26, P < 0.05; 0.77 ± 0.06 vs. 1.23 ± 0.03, t = −8.29, P < 0.05; and 0.68 ± 0.03 vs. 1.12 ± 0.12, t = −7.83, P < 0.05; F = 49.55, P < 0.001) and downregulated caspase 3 activating (0.23 ± 0.04 vs. 0.63 ± 0.06, t = −11.24, P < 0.05; 0.43 ± 0.03 vs. 0.74 ± 0.05, t = −8.86, P < 0.05; and 0.58 ± 0.03 vs. 0.80 ± 0.05, t = −6.17, P < 0.05; F = 100.15, P < 0.001), compared with light injury group. No significant change in the total level of caspase 3 was seen in different groups (F = 0.56, P = 0.75). As for inflammation, light injury significantly increased the expression of TNF-α (0.42 ± 0.04 vs. 0.25 ± 0.05, t = 5.99, P < 0.05; 0.65 ± 0.03 vs. 0.25 ± 0.05, t = 14.87, P < 0.05; and 0.86 ± 0.04 vs. 0.25 ± 0.05, t = 22.58, P < 0.05; F = 160.27, P < 0.001) and IL-1β (0.24 ± 0.01 vs. 0.19 ± 0.02, t = 2.33, P < 0.05; 0.35 ± 0.02 vs. 0.19 ± 0.02, t = 7.97, P < 0.05; and 0.48 ± 0.04 vs. 0.19 ± 0.02, t = 14.69, P < 0.05; F = 77.29, P < 0.001), compared with normal group. P-ERK1/2 inhibitor significantly decreased the overexpression of TNF-α (0.22 ± 0.02 vs. 0.42 ± 0.04, t = −7.40, P < 0.05; 0.27 ± 0.02 vs. 0.65 ± 0.03, t = −14.27, P < 0.05; and 0.33 ± 0.03 vs. 0.86 ± 0.04, t = −19.58, P < 0.05; F = 160.27, P < 0.001) and IL-1β (0.13 ± 0.03 vs. 0.24 ± 0.01, t = −5.77, P < 0.05; 0.17 ± 0.01 vs. 0.22 ± 0.02, t = −9.18, P < 0.05; and 0.76 ± 0.05 vs. 0.48 ± 0.04, t = −13.12, P < 0.05; F = 77.29, P < 0.001), compared with light injury group. Conclusion: The p-ERK1/2 inhibitor might protect the retina from light-induced photoreceptor degeneration and retinal inflammation.